Cloud Server Security System Design on Linux Almalinux 8.6 Operating System Based on WHM with DNS Management Using IP Masking Cloudflare - Chaedar Fatach, Muhamad Reza; Muhammad, Alva Hendi; Ariatmanto, Dhani (Journal of Electrical Engineering and Computer (JEECOM), 2025)
This study aims to design a Cloud Server Security System on the Linux Almalinux Operating System with DNS Management Using a Proxy Server Based on IP Masking Cloudflare using the Traffic Patterns and Packet Internet Gopher (PING) methods. The type of research used is qualitative research where researchers collect primary and secondary data. The results of the study concluded that this design can improve security in Cloud Servers. Before using IP Masking Cloudflare, server performance was low, Data Access and Management was Low, Scalability was Low, Access Security was Low, System Integration was Low, but after using IP Masking Cloudflare Server Performance, Data Access and Management, Scalability, Access Security, and System Integration increased.